Epidemiological profile of COVID-19: a parallel between Montes Claros, Minas Gerais and Brazil.: um paralelo entre Montes Claros, Minas Gerais e Brasil. - Soares, Kamila Teles; Bicalho, Ana Clara Soares; Araújo, Haiany Arielle Cangussu; Praes, Rafaella Calixto Vieira; Magalhães, Tatiana Almeida; Martins, Andréa Maria Eleutério de Barros Lima; Haikal, Desirée Sant'Ana (Revista Unimontes Científica, 2020)
Abstract: Objective: To describe epidemiological data related to the COVID-19 pandemic in Montes Claros, creating a parallel between the municipality, the state of Minas Gerais and Brazil. Methods: Descriptive study based on the daily collection of epidemiological data made available on the official websites of the Ministry of Health, the State Department of Health of Minas Gerais and Montes Claros between March 29th and August 17th. In addition, a parallel was created between two specific dates, with an interval of 45 days. Results: On June 30th, Montes Claros and Minas Gerais had a better epidemiological picture than Brazil, that reality changed on August 17th. Also an inversion in the epidemiological profile of confirmed cases was observed in the three locations, but the profile of deaths remained. Conclusion: It is believed that this study can contribute to the understanding of the epidemiological picture of COVID-19 in Montes Claros in a contextualized way.